PROSPECT THEORY AND DECISION UNDER RISK: A SYSTEMATIC LITERATURE REVIEW (2020-2026) - Linda Susilowati; Dwi Cahyaningdyah (Komunitas Manajemen Kompetitif, 2025)
Prospect Theory (PT) is one of the most influential theories in behavioral economic and financial psychology, explaining how individuals respond to uncertainty through loss aversion, probability weighting, and reference dependence. This article conducts a Systematic Literature Review (SLR) of 9 open-access international articles published in 2020–2025 that test decision-making behavior under risk using PT and Cumulative Prospect Theory (CPT). The extraction procedure uses the PRISMA protocol, with main categories: research context, theoretical model, empirical method, findings, and implications. The synthesis results show the consistency of loss aversion behavior, non-linear probability weighting, and framing effect that cause investors to deviate from rationality assumptions. The study also shows variations in elicitation parameters and methods, but generally confirms that risk preferences are influenced by psychological bias and market context. The theoretical implications emphasize the need for a decision model that considers behavioral bias, while practical implications recommend education-based and debiasing interventions to improve the quality of investment decisions. This review is limited to limited sample and methodological heterogeneity, and suggests future research to expand the empirical context and integration of experimental approaches.